Water‐Soluble Half‐Sandwich RuII–Arene Complexes: Synthesis, Structure, Electrochemistry, DFT Studies, and Aqueous Phase Hydroformylation of 1‐Octene. Issue 24 (1st July 2013) - Matsinha, Leah C.; Malatji, Peter; Hutton, Alan T.; Venter, Gerhard A.; Mapolie, Selwyn F.; Smith, Gregory S.
Abstract: Water‐soluble mononuclear ruthenium complexes containing monodentate P‐donor ligands [1, 3, 5‐triaza‐7‐phosphaadamantane (PTA) and P(OMe)3 ], together with a mononuclear bidentate salicylaldimine ruthenium–arene complex, were synthesized from a water‐soluble dimeric ruthenium(II)–arene precursor. These complexes were used as catalyst precursors in the aqueous biphasic hydroformylation of 1‐octene. Hydroformylation reactions with these Ru‐arene complexes showed that the complexes are active hydroformylation catalyst precursors in water. The catalyst precursors convert 1‐octene into a range of products, which include aldehydes and alcohols, as well as isomerization and hydrogenation products. The less basic the ligand, the more it favoured the production of aldehydes. The relative basicity of the ligands P(OMe)3, PTA and the N, O ‐chelating ligand was elucidated by cyclic voltammetry and supported by DFT calculations. The catalysts show good recyclability without a significant decrease in 1‐octene conversion. All of the catalysts could be reused three times. Abstract : Water‐soluble Ru II –arene complexes were synthesized and characterized by NMR and FTIR spectroscopy, mass spectrometry, elemental analysis and single‐crystal X‐ray crystallography. The water‐soluble Ru complexes catalyze the hydroformylation of 1‐octene, which they convert into aldehydes, alcohols, iso ‐octenes and octane. The catalysts could be recycled four times with sustained conversions and minimal Ru loss.